Effect of calcitriol combined with sevelamer carbonate on serum parathyroid hormone in patients with chronic renal failure - Zheng, Hui; Liu, Zhinan (Cellular and Molecular Biology, 2020)
This study aimed to observe and analyze the effect of calcitriol combined with sevelamer carbonate on serum parathyroid hormone in patients with chronic renal failure. This study included 180 patients who had been treated for chronic renal failure in our hospital were enrolled as research objects. The patients were randomly divided into two groups: a research group and a control group, each containing 90 cases. The research group was treated with calcitriol combined with sevelamer carbonate, and the control group was treated with calcitriol alone. The therapeutic effects of the two groups were observed and analyzed by SPSS 21. Comparing the levels of blood indexes (Ca, Cr, P, ALP, iPTH, TC, TG, LDL-C, HDL-C) of the two groups showed no significant difference between the two groups, P <0.05. Our results have the effect of different treatment regimens, the improvement effect of various blood indicators in the research group was significantly better than the control group, p<0.05. We concluded that the combined therapy of calcitriol and sevelamer carbonate in chronic renal failure patients can significantly improve the therapeutic effect, and at the same time actively improve the serum parathyroid hormone level, which is a treatment model that can be popularized and applied.